2013
DOI: 10.1590/brag.2013.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root and leaf applications of soluble silicon on blast development in rice

Abstract: Blast, caused by Pyricularia oryzae, is the most important fungal disease of rice worldwide. This study aimed to compare root and foliar supply of soluble silicon (Si) on rice resistance to blast. The application of soluble Si to the roots increased Si concentration in leaf tissues as compare to plants grown in soil amended with calcium silicate. There was no increase in leaf Si concentration after soluble Si spray, regardless if the leaves were washed or not before analysis. X-ray microanalysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…Previous research reported that thrips (Frankliniella schultzei) as an insect vector of Tomato spotted wilt virus (TSWV) in Brazil, was able to be suppressed by the application of silica (Almeida et al, 2009). The application of silica could also suppress Pythium aphanidermatum infected the roots of tomato plants (Heine et al, 2007) and Pyricularia oryzae caused blast disease in rice (Cacique et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reported that thrips (Frankliniella schultzei) as an insect vector of Tomato spotted wilt virus (TSWV) in Brazil, was able to be suppressed by the application of silica (Almeida et al, 2009). The application of silica could also suppress Pythium aphanidermatum infected the roots of tomato plants (Heine et al, 2007) and Pyricularia oryzae caused blast disease in rice (Cacique et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…O suprimento de Si para plantas tem reconhecida importância para a redução da intensidade de várias doenças em importantes culturas comerciais, principalmente para o arroz (Cacique et al, 2013;Cruz et al, 2013Cruz et al, , 2014Datnoff et al, 1997;Fortunato et al, 2014;Rodrigues et al, 2003a,b;Schurt et al, 2013;Tatagiba et al, 2014). No entanto, o presente trabalho apresenta as primeiras evidências, a nível microscópico, de que a resistência do arroz à queima das bainhas é potencializada pelo Si.…”
Section: Discussionunclassified
“…Kim et al (2002) sugeriram que folhas de arroz com maior concentração de Si formaram uma barreira que impediu a penetração de P. oryzae. Outros estudos utilizando microanálise de raios-X também associam alto acúmulo de Si na superfície de folhas de arroz e de trigo com maior resistência às doenças (Cacique et al, 2013;Domiciano et al, 2010;Guével et al, 2007;Rezende et al, 2009). No presente estudo, intensa e homogênea deposição de Si nas bainhas das plantas de arroz de ambos cultivares atuaram, provavelmente, como uma barreira física, afetando a penetração e a colonização de R. solani.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Epstein 2001citou alguns exemplos de ações benéficas que o silício é capaz de promover na planta, em casos cientificamente comprovados, tais como: resistência ao ataque de organismos patogênicos; melhor estruturação da arquitetura das plantas; resistência à herbivoria de insetos fitófagos; redução da fitotoxidez das plantas causadas por metais pesados, entre outras. De acordo com Cacique et al (2013), o fornecimento de Si para plantas de arroz, tanto na forma solúvel aplicada nas raízes ou a sua pulverização sobre a parte aérea, pode aumentar a resistência das plantas ao ataque de fungos. Segundo Pinto et al (2009), a adição do Si ameniza o efeito negativo de metais pesados, como por exemplo o excesso de Zn sobre o crescimento de plantas de Eucalyptus urophylla e proporciona uma utilização mais eficiente de P, Ca, Mg e S por estas plantas.…”
Section: Introductionunclassified